Keggin ion mediated synthesis of hydrophobized pd nanoparticles for multifunctional catalysis - Mandal, Sujata; Das, Amitava; Srivastava, R.; Sastry, M. (Langmuir, 2005)
Development of simple and reliable protocols for the synthesis of organically soluble catalytically active metal nanoparticles is an important aspect of research in nanomaterials. We demonstrate herein the formation of Pd nanoparticles by reduction of aqueous Pd(NO3)(2) by photoexcited Keggin ions (phosphotungstate anions). This results in the formation of Pd nanoparticles capped with with Keggin ions that render the particles negatively charged. The Keggin ion capped Pd nanoparticles may then be phase transferred into nonpolar organic solvents such as toluene by electrostatic complexation with cationic surfactants such as octadecylamine at the liquid-liquid interface. This results in a new class of catalyst wherein both the Pd core and Keggin ion shell may be used in a range of catalytic reactions leading to a truly multifunctional catalyst dispersible in organic solvents.